Students Language Awareness in English Classroom of English Education Study Program - Audriyan Audriyan; Hilma Pami Putri (Universitas Pahlawan Tuanku Tambusai, 2021)
Despite their designation as students of the English Education Department who are meant to teach English to others, many of these students rarely use English both inside and outside the classroom. This phenomenon’s prevalence in Indonesia makes students unaware of their mistakes when using English. The purpose of this study is to analyze the language awareness of sixth-semester students through the five language awareness domain to provide insight into the importance of language awareness in the classroom, especially for students of this particular type of department. This study used random sampling and using a questionnaire with fifteen items collected from 108 responses. This analyzed their language awareness through the five domains of language awareness, namely the affective, social, power, cognitive, and performance domains. Results showed that 86.67% of students had the affective domain from the social domain was 81.62%, from the power domain was 73.13%, from the cognitive domain was 75.96%, and from the performance domain was 65.86%. The overall value of the five domains is 76.65% showed that students have good language awareness. It means language awareness of students IS pretty good inside the classroom.